Reception Audiens Ibu Rumah Tangga Muda Terhadap Presenter Effeminate dalam Program-program Musik Televisi - DEWI K. N, IDA NURAINI (Komunikator, 2012)
It is true that effeminacy or transgender still become a kind of social deviation. However, it seems that their existence is increasingly accepted by the society. This is indicated by the number of media which use effeminate figures in entertainment industry and television. This study is a reception analysis of young housewifes towards effeminate presenters on Music Television’s programs. The purpose of this study is to understand young housewifes acceptance towards effeminate presenters on Music Television’s programs which recently have become one of the most popular programs in several television stations. This study also attempts to reveal the factors that affect their acceptance towards effeminate presenters. The theoretical framework used in this study is the audience analysis and the factors that influence the acceptance. On the other hand, the method used in this research is the fracture method and faction method. This study reveals that the position of the housewives as the figures who are responsible for all domestic tasks has become one of the factors that have strong influence in taking a position of decoding negotiation. There are three correlated aspects which intensely affect the position of decoding information which are economic factors, social relation, and media related to entertainment. Keywords: reception analysis, housewives, effeminate